THE ROLE OF EDUCATION FOR SUSTAINABLE DEVELOPMENT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article contains the information about the ecological station in the world andin the mountainous region of Central Asia. It was shown that, the rapid increase of negative anthropogenic impacts in recent years leads more to the destruction of the natural ecosystem. Forthe effective resolving of the problems the system of functions is regional the realization of whichcan improve to definition extent the ecological situation and favors the mountainous of ecologicalbalance in the nature. It is also suggested the elaboration and applying the new approaches andconception of the relationships between human and the environment, and also the completion ofcurriculum and educational programmers with conception of stable improvement and the controlover the internal resources’.
Keywords: Ecological balance, ecosystem, degradation, greenhouse effect, environmental strategy, environmental accounting, environmental control.